Equilibrium in a Non-Interest Open Economy. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
This paper analyzes an economy in which there are no interest-bearing assets, only equity shares. Equilibrium conditions are derived for the case of a closed economy, an open economy with trade in goods only, and finally one with trade in both goods and equity shares. It is shown that the rate of return to capital equilibrates savings and investment, that the differential between the domestic and foreign rates of return to equity determines the direction of capital flows, and that under a fixed exchange rate system, adjustments induced by exchange rate changes are channeled through the asset accounts.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet